DEFINITION OF ZALEPLON, ZOLPIDEM AND ZOPICLON IN BIOLOGICAL OBJECTS - V. A. Kartashov; G. P. Chepurnaya; L. V. Chernova (Разработка и регистрация лекарственных средств, 2019)
Soporific substances of the third generation - Z-preparations: Zaleplon (Andante), Zopiclone (Imovane) and Zolpidem (Ivadal) - are widely used in medicine for the treatment of insomnia. Despite a number of advantages over of barbiturate derivatives and 1,4-benzodiazepine, the identified preparations are toxic. Poisoning incidents, including fatalities, are described. To diagnose intoxications by these medicines and other purposes (for monitoring the concentration of these medicines in the blood, studying pharmacokinetics, evaluating drug interactions, optimizing treatment control), the development of methods for defining Z-preparations in biological objects becomes important, that is currently developed insufficient. Therefore, the purpose of this work is to study and analyze the specialized literature on the chemical, physico-chemical, pharmacological properties, methods of analysis of investigated substances, methods of extraction, purification, methods of identification and quantification while studying the biological objects.